2014
DOI: 10.1016/j.media.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of white and gray matter geometry: A framework for investigating brain development

Abstract: Current neuroimaging investigation of the white matter typically focuses on measurements derived from diffusion tensor imaging, such as fractional anisotropy (FA). In contrast, imaging studies of the gray matter oftentimes focus on morphological features such as cortical thickness, folding and surface curvature. As a result, it is not clear how to combine findings from these two types of approaches in order to obtain a consistent picture of morphological changes in both gray and white matter. In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Extended on this, based on previous literature and our results, we have summarized the dynamics of the expected microstructural changes triggered following a TBI in the white matter (Figure 6). We suggest that controlled cortical impact affects the physiological and biomechanical properties of gray and white matter that can be detected using non-invasive imaging tools (80,81). In the step (i) and (ii) of Figure 6, we demonstrated that the axons that were normal before injury appear to be swollen within 5 h post-injury that has stretched the myelin sheath reflected by increase the radial diffusivity (perpendicular) without any change in the axial (parallel) diffusivity (82) (Figure 1).…”
Section: Pathology Associated With Fiber Tracking and Demyelination Pmentioning
confidence: 99%
“…Extended on this, based on previous literature and our results, we have summarized the dynamics of the expected microstructural changes triggered following a TBI in the white matter (Figure 6). We suggest that controlled cortical impact affects the physiological and biomechanical properties of gray and white matter that can be detected using non-invasive imaging tools (80,81). In the step (i) and (ii) of Figure 6, we demonstrated that the axons that were normal before injury appear to be swollen within 5 h post-injury that has stretched the myelin sheath reflected by increase the radial diffusivity (perpendicular) without any change in the axial (parallel) diffusivity (82) (Figure 1).…”
Section: Pathology Associated With Fiber Tracking and Demyelination Pmentioning
confidence: 99%
“…Recent results have shown that, albeit tractography can extract large white matter fascicles from DW‐MRI, there is a high incidence of erroneous streamlines (false positives) resulting from current tractography algorithms [Côté et al, ; Jbabdi et al, ; Jones, ; Maier‐Hein et al, ; Thomas et al, ]. This is largely due to complex ambiguous local fiber configurations (e.g., crossing, kissing, or fanning) [Maier‐Hein et al, ; Savadjiev et al, ]. Furthermore, the relationship between the resulting streamlines and the underlying white matter microstructure characteristics, such as axon diameter, remains poorly understood [Jones, ].…”
Section: Introductionmentioning
confidence: 99%
“…We have made the choice of connecting neighboring GM and WM regions with an edge as there is increasing evidence that the tissue and geometric properties of proximal GM/WM regions are stongly related Miyata et al (2009); Koch et al (2013); Liu et al (2014); Savadjiev et al (2014). Furthermore, the graph is only a guide for the precision matrix estimation process.…”
Section: A Priori Graphmentioning
confidence: 99%